The difference between epidermoid cysts and ranula in durante operation: A case report - Verry Herawan; Wenny Yulvie; Mohammad A. Latief (Journal of Dentomaxillofacial Science, 2021)
Objective: Marsupialization is therapy for ranulas but sometimes in determining the diagnosis with epidermoid cysts like to be wrong. Epidermoid cysts in the mouth, especially at the base of the tongue, have clinical features similar to those of ranula. In the operating durante we can find the difference. For that we need a more careful examination and in determining the diagnosis of epidermoid cysts with ranula. Methods: a 16-year-old male has a lump under the tongue since the age of 2.5 years as big as a marble. Since 1 month ago the lump was getting bigger and causing the tongue to be bitten frequently, difficulty speaking and pain relapsing in lumps. We perform therapy with biopsy excision where previously we will marsupialization. Results: Epidermoid cyst found during surgery previously diagnosed with ranula Conclusion: Precisely distinguishing epidermoid and ranular cysts requires a complete clinical examination and interview with the patient. So that surgical therapy such as marsupialization and biopsy excision can be selected